English Writing Correction Based on Intelligent Text Semantic Analysis - Shuang Yang (Advances in Multimedia)
In order to improve the teaching effect of English writing, this paper combines the intelligent text semantic analysis algorithm to construct an English writing correction model. Moreover, this paper deduces the relationship formula between the range of English semantic information cloud drop and the evaluation word through the contribution of cloud drop group to qualitative concepts, the association between cloud drop central area and evaluation words, and the relationship between cloud drop ring area and evaluation word. In addition, this paper uses the word selection probability results obtained from the preference evaluation. The simulation results show that the English writing correction model based on intelligent text semantic analysis proposed in this paper can play an important role in the intelligent teaching of English writing.